(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2019)
The ITEM, Instut des Textes et Manuscrits Modernes, celebrated 50 years of activity with a major congress held in Paris from 17th to 20th October 2018: "La critique génétique comme processus". The meeting offered the opportunity to retrace the history of the Parisian laboratory, cradle of the critique génétique, and to draw up a balance of 50 years of activity.